Influence of Replacement of Maize by Wheat Bran in Diet on Cost of Production in Pigs - Elanchezhian, N.; Ally, K. (Indian Journal of Animal Nutrition, 2018)
The experiment was conducted to assess the effect of replacement of maize by different levels of wheat bran on cost of production in Large White Yorkshire (LWY) pigs. Thirty weaned piglets were randomly divided into three groups and were allotted to the three dietary treatments as control ration (T1) as per NRC, 1998 and maize of control ration was replaced by wheat bran by 50% (T2) and 100% (T3) for a period of 70 days. Cost of production per kg weight gain was calculated based on body weight gain, total feed intake and feed cost toarrive at the economics of production. The body weight gain and total feed intake recorded were 56.91, 53.89, 47.49 kg and 159.28, 154.98, 145.98 kg, whereas cost per kg feed and cost of feed per kg body weight gain were` 17.56, 17.13, 16.75 and ` 49.09, 49.23, 51.54, respectively in groups T1, T2 and T3. The result of this study revealed that 50% of maize in the ration can be replaced by wheat bran (T2) without affecting growth performance and cost of production per kg weight gain in Large White Yorkshire pigs and was comparable with control group, hence, it is preferred in time of scarcity of maize. Whereas 100% replacement of maize by wheat bran reduced growth performance and increased cost of production.